The issuance of going concern opinion process in companies that hire specialized auditors - Osman, Mohammad Noor Hisham; Abdul Latiff, Ahmed Razman; Ong, Tze San
It is the responsibility of auditors to assess clients' financial viability and to issue going concern opinion (GC opinion) if there is doubt about the ability of the clients to continue operation in the near future, according to ISA 570. The responsibility to issue GC opinion appropriately is not to burden auditors to predict the future of clients instead to send a signal to stakeholders so that the later could safe from financial losses in the case of sudden companies collapse. However, there are still incidents locally and internationally in which auditors do not issue GC opinion to financially distress companies. The objective of this study is to examine the practice of GC opinion issuance in listed companies that hire specialized auditors. The findings suggest that there is no direct relationship between specialized auditors and the probability to issue GC opinion. However, this study discovers that the higher the management ownership in a client company the less likely the specialized auditor will issue GC opinion. These findings provide evidence for contention made in Callaghan, Parkash and Singhal (2009) that management can negatively influence the probability of auditor to issue GC opinion.